Propuesta de Agroturismo para el Cantón Puyango, Provincia de Loja. - Gordillo Enriquez, Josselyn Yosmery (2023)
The Puyango canton has great wealth of agricultural, agro-industrial and livestock resources to put them in value and develop tourist activities aimed at benefiting small entrepreneurs. In view of the agrotourism potential, it was determined to develop this research work, for which the general objective was: "Design an agrotourism proposal for the Puyango Canton, Loja province." Which was developed based on the following objectives: Diagnose the current situation of agrotourism in the Canton Puyango, Province of Loja. Carry out the design of an agrotourism proposal for the Puyango Canton, Loja Province. Propose tourism promotion strategies for the agrotourism proposal in the Puyango canton, Loja Province. For the development of the research, the methodology of Marvin Blanco (2019) Design and operation of agrotourism products proposed by the ICCA was used, which allowed a multidimensional analysis of the territory, identify tourist attractions, tourist services, and create agrotourism products. Likewise, the direct observation technique was applied for the collection of information on the agrotourism offer, simple and crossed SWOT, surveys and interviews. The results obtained were fifteen places where agricultural and livestock activities are offered. The tourist profile is summarized in married people from El Oro, Loja and Guayas between 36 and 45 years old, willing to buy agrotourism products with a value between $51 and $60. Therefore, the proposal is based on the development of an agrotourism circuit and an agrotourism route. Therefore, the MINTUR Manual for the generation of tourist routes and itineraries was used for their development. As strategies that will help disseminate the proposal, the following were obtained: tourism promotion through brochures, blogs, social networks, billboards and agrotourism fairs. In conclusion, the Puyango canton has sufficient agrotourism resources for the creation of products that, supported by the actors involved and the necessary promotion, can begin to develop new tourism alternatives.